Prolonged Sitting Interrupted by 6-Min of High-Intensity Exercise: Circulatory, Metabolic, Hormonal, Thermal, Cognitive, and Perceptual Responses - Sperlich, Billy; De Clerck, Ine; Zinner, Christoph; Holmberg, Hans-Christer; Wallmann-Sperlich, Birgit (Frontiers in Physiology, 2018)
The aim was to examine certain aspects of circulatory, metabolic, hormonal, thermoregulatory, cognitive, and perceptual responses while sitting following a brief session of high-intensity interval exercise. Twelve students (5 men; age, 22 ± 2 yrs) performed two trials involving either simply sitting for 180 min (SIT) or sitting for this same period with a 6-min session of high-intensity exercise after 60 min (SIT+HIIT). At T0 (after 30 min of resting), T1 (after a 20-min breakfast), T2 (after sitting for 1 h), T3 (immediately after the HIIT), T4, T5, T6 and T7 (30, 60, 90 and 120 min after the HIIT), circulatory, metabolic, hormonal, thermoregulatory, cognitive, and perceptual responses were assessed. The blood lactate concentration (at T3-T5), heart rate (at T3-T6), oxygen uptake (at T3-T7), respiratory exchange ratio, and sensations of heat (T3-T5), sweating (T3, T4) and odor (T3), as well as perception of vigor (T3-T6), were higher and the respiratory exchange ratio (T4-T7) and mean body and skin temperatures (T3) lower in the SIT+HIIT compared SIT trial. Levels of blood glucose and salivary cortisol, cerebral oxygenation, and feelings of anxiety/depression, fatigue or hostility, as well as the variables of cognitive function assessed by the Stroop test did not differ between SIT and SIT+HIIT. In conclusion, interruption of prolonged sitting with a 6-min session of HIIT induced more pronounced circulatory and metabolic responses and improved certain aspects of perception (i.e., vigor), without affecting hormonal, thermoregulatory or cognitive functions.